Performance testing of cross flow heat exchanger operating in the atmosphere of flue gas particulate with vapor condensation - A. Nuntaphan (2018)
Performance testing of a cross flow heat exchanger operating under the atmosphere of flue gas particulate from combustion was carried out in this work. This heat exchanger exchanges heat between flue gas from the fuel oil combustion and cold water. The heat exchanger is composed of a spiral finned tube bank having 3 rows and 8 tubes per row with a staggered arrangement. The fin spacings considered are 2.85 and 6.10 mm. The theories of thermodynamics and heat transfer are used for analyzing the performance of this system. In this experiment, the flue gas temperature of 200°-C from combustion having 0.35 kg/s mass flow rate flows along outside surface of the heat exchanger and transfers heat to the 25°-C cooling water having 0.15 kg/s mass flow rate flowing in the tube side. Each experiment uses 750 hr for testing. During the testing, part of flue gas condenses on the heat transfer surface. From the experiment, it was found that the heat transfer rate of both heat exchangers tended to decrease with time while the airside pressure drop increased. These results come from the fouling on the heat transfer surface. Moreover, it is found that the heat exchanger having 2.85 mm fin spacing has an approximately 4 times higher fouling resistance than that of the 6.10 mm fin spacing. In this work a model for calculating the fouling resistance is also developed as a the function of time. The model is developed from that of Kern and Seaton and the mean deviation of the model is 0.789.